RANCANGAN SISTEM INFORMASI MONITORING DAN EVALUASI KIT SANITARIAN PUSKESMAS - Dwita Maulida; Artha Prabawa (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Environmental health inspection is part of the environmental health services carried out by the Public Health Center. Environmental health inspections are carried out by observing environmental media using the health center's sanitarian kit to measure the quality of water, air and food. The District/City Health Office is expected to assist the Public Health Center in providing a sanitarian kit as a tool to support environmental health inspections. The Public Health Center that already have a sanitarian kit, need to carry out item management which includes monitoring and evaluating the use of the equipment. Based on this, the design of a monitoring and evaluation information system for the health center sanitarian kit using the Systems Development Life Cycle (SDLC) method with a prototype approach was created. System design stages start from planning, analysis, to design. The end result of this information system is to obtain information related to the utilization of the kit, the condition of the equipment, the obstacles encountered, to the maintenance of the equipment (calibration, availability of reagents and spare parts) which can then be utilized by the District/City Health Office and the Ministry of Health.